The Performance of Agricultural Extension Workers to Increase the Knowledge of Corn Farmers in Barakati Village, Batudaa District, Gorontalo Regency - Hendra Kurniawan; Zainal Abidin; Ulfira Ashari (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
Agricultural extension is a non-formal education for farmers. This study aims to determine the performance of agricultural extension workers on corn farmers in Barakati Village, Batudaa District, Gorontalo Regency. The method used in this study is data tabulation using a Likert scale. The sample in this study was 63 people. The results of this study, namely the performance of agricultural extension workers in the form of increasing knowledge of corn farmers in Barakati Village, Batudaa District, Gorontalo Regency, were quite good from the overall number of results, reviewed from the intensity of counseling with a percentage of 56.44%, reviewed the extension method with a percentage of 53.33%, in terms of counseling media with a percentage of 61.01